Conceptual simulation design - Ochwa, Michael O (Cranfield University, 2007)
The work presented in this thesis considers the issues related to the design and implementation of the rotor blade production facility at Rolls-Royce. The volume production of this component will be significantly higher than Rolls Royce has ever delivered on similar projects. As a result, a future factory consisting of process lines and manufacturing cells will be built. The issue considered includes the evaluation of various factory designs and layout techniques that will improve production flow, optimal capacity utilization, and minimum work-in- process and lead-times. The subject of manufacturing cells verses machine utilization was also considered. This factory design and selection analysis was supported by extensive research comprising literature review and simulation study of various manufacturing layouts including cellular, job-shop type functional layout and hybrid configurations. Therefore, this study provides a basis to properly carry out analysis of the current Rolls-Royce production facilities and subsequently the preliminary conceptual simulation design of the future factory to manufacture L-Generic-blisk and F-Generic-blisk drive engine compressor Generic-blisk. A number of cell and flow-line design concepts were analysed with a succession of flexible Witness models (configured and driven by Microsoft Excel) and used to analyse the flow and productivity, to support a sustained growth in production volumes and maturation of process.